Pemahaman Mahasiswa tentang Keberlanjutan dalam Kimia: Kajian Pengembangan pada Proyek Green Chemistry - Azzajjad, Muhammad Fath; Ahmar, Dewi Satria; Kilo, Ahmad Kadir (Jambura Journal of Educational Chemistry, 2024)
Students who have a strong understanding of concepts, good use of terminology, and the ability to invent environmentally friendly products, they can become effective drivers of change. This will enable them to support Green Chemistry innovations and practices in the future. provides practical experience to students, allows them to use the ideas they learn in real-life situations, and encourages them to show greater concern for environmental sustainability. This survey study took a sample of 28 individuals. Students' understanding of the concept of Green Chemistry is still in the "fairly good" category, with an average of 1.83. However, this is a good result, and their understanding can still be improved with more in-depth learning methods and greater emphasis on this concept in the curriculum. A good understanding of Green Chemistry terminology was positive, with an average of 2.58. This shows that students can communicate well using relevant words in the field of green chemistry; this is crucial for participating in discussions and developing sustainable projects. In addition, students' ability to find environmentally friendly items is quite good, with a mean of 2.36. Improving this ability continuously can help them support more sustainable products and practices in their daily lives.